The Calcium Channel C-Terminal and Synaptic Vesicle Tethering: Analysis by Immuno-Nanogold Localization - Chen, Robert H. C.; Li, Qi; Snidal, Christine A.; Gardezi, Sabiha R.; Stanley, Elise F. (Frontiers in Cellular Neuroscience, 2017)
At chemical synapses the incoming action potential triggers the influx of Ca2+ through voltage-sensitive calcium channels (CaVs, typically CaV2.1 and 2.2) and the ion binds to sensors associated with docked, transmitter filled synaptic vesicles (SVs), triggering their fusion and discharge. The CaVs and docked SVs are located within the active zones (AZ) region of the synapse which faces a corresponding neurotransmitter receptor-rich region on the postsynaptic cell. Evidence that the fusion of a SV can be gated by Ca2+ influx through a single CaV suggests that the channel and docked vesicle are linked by one or more molecular tethers (Stanley, 1993). Short and long fibrous SV-AZ linkers have been identified in presynaptic terminals by electron microscopy and we recently imaged these in cytosol-vacated synaptosome ‘ghosts’. Using CaV fusion proteins combined with blocking peptides we previously identified a SV binding site near the tip of the CaV2.2 C-terminal suggesting that this intracellular channel domain participates in SV tethering. In this study we combined the synaptosome ghost imaging method with immunogold labeling to localize CaV intracellular domains. L45, raised against the C-terminal tip, tagged tethered SVs, often as far as 100 nm from the AZ membrane whereas NmidC2, raised against a C-terminal mid-region peptide and C2Nt, raised against a peptide nearer the C-terminal origin, resulted in gold particles that were proportionally closer to the AZ. Interestingly, observation of gold-tagged SVs with NmidC2 suggests a novel SV binding site in the C-terminal mid region. Our results implicate the CaV C-terminal in SV tethering at the active zone with two possible functions: first, capturing SVs from the nearby cytoplasm and second, contributing to the localization of the SV close to the channel to permit single domain gating.